Menguatkan Akidah dan Kualitas Hidup melalui Pembinaan Pemahaman Agama Islam dalam Kegiatan Muharoman di Masjid Al-Hidayah Kujangsari - Hanipudin, Sarno; Subki, Taqiyudin; Mulat, Tri (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
This dedication is motivated by the awareness of the importance of providing a comprehensive understanding of the teachings of Islam to the community. Misunderstandings can have negative effects on both the religion itself and the community. Therefore, proper guidance is needed with the right approach, both in terms of content, methods, and language of communication. Al-Hidayah Mosque in Kujangsari village was chosen as the location for this dedication project for several reasons, including having a large congregation and being a center for religious activities in the village. The target of this dedication is the 150 members of the Al-Hidayah Mosque congregation. The dedication was carried out using a teaching approach through Muharoman activities with a lecture method. The results of the dedication showed satisfactory outcomes, where the participants increased their religious awareness and understanding of the teachings of Islam.